Comparison of protective effects of teneligliptin and luseogliflozin on pancreatic β-cell function: randomized, parallel-group, multicenter, open-label study (SECRETE-I study) - Shimoda, Masashi; Katakura, Yukino; Mashiko, Akiko; Iwamoto, Masahiro; Nakanishi, Shuhei; Anno, Takatoshi; Kawasaki, Fumiko; Obata, Atsushi; Fushimi, Yoshiro; Sanada, Junpei; Kohara, Kenji; Isobe, Hayato; et al. (Frontiers in Endocrinology, 2024)
The aim of this study is to directly compare the effects of SGLT2 inhibitors and DPP-4 inhibitors on β-cell function in patients with type 2 diabetes.We conducted a 26-week, randomized, open-label, parallel-group study, including a 1-2 week drug washout period, in patients with type 2 diabetes with HbA1c ≥7.0% and <9.0% and BMI ≥20 kg/m 2 despite treatment with a drug naïve or other than DPP-4 inhibitors or SGLT2 inhibitors. A total of 103 subjects were randomly assigned to receive once daily oral luseogliflozin (L) or teneligliptin (T). The primary endpoint was the effect of L vs. T on the change in log-transformed (Ln) disposition index (DI) (DI 0-120min; combining measures of insulin secretion and sensitivity) from baseline to week 25-26 (post intervention), which was calculated by conducting an oral glucose tolerance test.Results: Ln DI 0-120min were improved in both groups: -0.46±0.68 to -0.20±0.59 (p=0.03) in L group and -0.26±0.60 to -0.05±0.62 (p=0.01) in T group. The change in Ln serum proinsulin/CPR ratio, a marker of β-cell dysfunction, was reduced in L group (1.63±0.63 to 1.56±0.68, p=0.16), but rather increased in T group (1.70±0.75 to 1.90±0.51, p=0.01), with significant difference between the two groups (-0.27; p=0.004).Conclusions: Improvement of disposition index in subjects with obese type 2 diabetes was comparable between luseogliflozin and teneligliptin. On the other hand, it is likely that alleviation of β-cell dysfunction is more effective with luseogliflozin compared to tenegliptin.